Losing supramolecular orientational memory via self-organization of a misfolded secondary structure. Issue 18 (3rd April 2018) - Sahoo, Dipankar; Peterca, Mihai; Aqad, Emad; Partridge, Benjamin E.; Klein, Michael L.; Percec, Virgil
Abstract : Comparing the self-organization of two dendronized perylene bisimides reveals how structurally defective primary structure eliminates memory function via hierarchical self-organization. Abstract : Supramolecular orientational memory (SOM) provides a route to otherwise inaccessible nanoscale architectures for certain molecules. In these privileged cases, columnar domains organized from self-assembling dendrons undergo reorientation during heating to, and subsequent cooling from, a 3D phase composed of "spheres", such as a body-centered cubic phase or a Pm 3̄ n cubic phase, known also as Frank-Kasper A15. The directions of the reoriented columns preserve key interactions from the preceding cubic phase. However, SOM was observed so far in a very limited number of assemblies. The molecular determinants enabling SOM, and its generality, remain poorly understood. Here we report the synthesis and structural and retrostructural analysis of a perylene bisimide (PBI) with two self-assembling benzyl ether dendrons, 3, 5-G2-PBI, and compare its assemblies with those of a previously reported PBI, 3, 4, 5-G2-PBI, which exhibits SOM and has an additional minidendritic building block in its dendrons. The removal of this minidendron in 3, 5-G2-PBI eliminates its ability to self-assemble into supramolecular spheres and organize into a cubic phase, thereby precluding 3, 5-G2-PBI from exhibiting SOM. This finding demonstrates hierarchical transfer of structural information from primary structure to material function, analogous to the misfolding of proteins into toxic structures such as those implicated in Alzheimer's and Prion diseases. The concepts exemplified here provide new insights into the hierarchical basis for SOM and will aid in the translation of the SOM concept to a broader diversity of soft matter such as block copolymers and surfactants.